Strategi Pengembangan Tabungan Qurban Pada Lembaga Amil Zakat Infaq dan Shadaqah Muhammadiyah (Lazismu) Jember - Sebastiana Viphindrartin; Margaretha Ardhanari; Ritna Ilmala Sari; Ahmad Ahsin Kusuma (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
This research aims to find out the Tabungan Qurban development strategy at LAZISMU Jember. Development strategies are needed to formulate the right alternative strategies to be applied to Tabungan Qurban LAZISMU Jember. This research uses descriptive analytical research methods. Data collection methods are interviews with questionnaires, observations and documentation. The data analysis method used is to use SWOT analysis through three stages, identification of internal factors and external factors, input stage and matching stage. The results of the analysis showed that the development of Tabungan Qurban LAZISMU Jember by using SWOT analysis include: strengths-opportunities (maintaining the image of the institution in the eyes of donors and building a positive image in the community and increasing loyalty to donors, while maintaining the quality of qurban meat by maximizing the empowerment of qurban breeders, maximizing cooperation with Islamic banking, determining brand positioning statements), weaknesses-opportunities (forming a special deviation to handle and manage savings programs, promote on social media in an orderly manner), strengths-threaths (increasing the competitiveness of more institutions than other institutions), weaknesses-threaths (utilizing LAZISMU human resources to improve the quality of Tabungan Qurban). Keywords: Tabungan Qurban, SWOT Analysis, Development Strategy